2023
DOI: 10.3390/ijms24054588
|View full text |Cite
|
Sign up to set email alerts
|

R-Propranolol Has Broad-Spectrum Anti-Coronavirus Activity and Suppresses Factors Involved in Pathogenic Angiogenesis

Abstract: The SARS-CoV-2 pandemic highlighted the need for broad-spectrum antivirals to increase our preparedness. Patients often require treatment by the time that blocking virus replication is less effective. Therefore, therapy should not only aim to inhibit the virus, but also to suppress pathogenic host responses, e.g., leading to microvascular changes and pulmonary damage. Clinical studies have previously linked SARS-CoV-2 infection to pathogenic intussusceptive angiogenesis in the lungs, involving the upregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…We next evaluated the efficacy of 1,6- epi -cyclophellitol cyclosulfate 11 , in comparison to our most potent iminosugar, naphthyl-deoxynojirimycin 2 , as well as Miglustat 1 in a more advanced model of primary human bronchial epithelial cells that were cultured at the air–liquid interface (ALI-PBEC), as we described previously. , Thus, ALI-PBEC cells were infected with SARS-CoV-2 (10 5 PFU per insert; estimated MOI ∼0.1) and treated with compounds on the apical side of the cells for 2 h. For uninfected controls, PBS was used instead of virus. The compounds were also present in the basal medium during the whole experiment until 48 hpi, when samples were harvested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next evaluated the efficacy of 1,6- epi -cyclophellitol cyclosulfate 11 , in comparison to our most potent iminosugar, naphthyl-deoxynojirimycin 2 , as well as Miglustat 1 in a more advanced model of primary human bronchial epithelial cells that were cultured at the air–liquid interface (ALI-PBEC), as we described previously. , Thus, ALI-PBEC cells were infected with SARS-CoV-2 (10 5 PFU per insert; estimated MOI ∼0.1) and treated with compounds on the apical side of the cells for 2 h. For uninfected controls, PBS was used instead of virus. The compounds were also present in the basal medium during the whole experiment until 48 hpi, when samples were harvested.…”
Section: Resultsmentioning
confidence: 99%
“…RNA was isolated by magnetic bead isolation, as described in ref . Equine arteritis virus (EAV) in AVL lysis buffer (Qiagen) was spiked into the isolation reagent as an internal control for extracellular RNA samples.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of oral pamapimod with pioglitazone on COVID-19 development and recovery in non-hospitalised patients infected with SARS-CoV-2 is currently being investigated in a Phase II clinical trial (KIN-FAST trial, NCT05659459). On the other hand, Thaler et al [ 6 ] show that R-propranolol exhibits broad-spectrum anti-coronavirus activity, inhibiting the replication of MERS-CoV, SARS-CoV and SARS-CoV-2 in several cell lines and in human primary bronchial epithelial cells. Using time-of-addition assays, the authors show that R-propranolol inhibits an unidentified post-entry step of the SARS-CoV-2 replication cycle, likely via a host cell factor.…”
mentioning
confidence: 99%
“…SARS-CoV-2 infection leads to pathogenic blood vessel formation in the lungs (intussusceptive angiogenesis), which is associated with the upregulation of pro-angiogenic factors such as ANGPTL4 and VEGFA [ 8 ]. Thaler et al [ 6 ] also investigated the effect of propranolol on ANGPTL4 expression. They found that SARS-CoV-2 upregulated ANGPTL4 in endothelial and other cells, which was suppressed by R-propranolol in a process that was partially independent of the antiviral effect.…”
mentioning
confidence: 99%